Recent Progress on Black Phosphorus‐Based Materials for Photocatalytic Water Splitting. Issue 12 (6th September 2018) - Yan, Junqing; Verma, Priyanka; Kuwahara, Yasutaka; Mori, Kohsuke; Yamashita, Hiromi
Abstract: Employing photocatalytic technology for efficient water splitting to hydrogen evolution is a sustainable and renewable solution for energy and environmental issues. Large‐scale utilization of solar hydrogen requires the appropriate usage of photocatalysts with high efficiency and their easy integration into solar devices. Recently, 2D materials have been widely studied because of their potential utility in device fabrication. Black phosphorus (BP) is a newly developed 2D direct bandgap semiconductor with an impressive tunable bandgap and fast carrier migration characteristics. In this review, the optical and electronic characteristics of 2D phosphorene‐based materials are mainly discussed in terms of water splitting reaction. Density functional theory calculations are first summarized, followed by brief discussions on the direct application of BP in photocatalytic water splitting based on recent reports. This review might assist researchers to design new materials for photocatalytic water splitting. Abstract : Black phosphorus (BP) is an interesting and promising 2D candidate for energy conversion and storage. This review focuses on photocatalytic water splitting of BP‐based samples from the view of theoretical calculation and experimental aspects. This review could help researchers design new materials for photocatalytic water splitting.